Exploring Perception, Implementation, and Appropriateness: A Qualitative Case Study of Indonesian English Teachers' Practices in English Language Assessment - Ngadiso (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Assessment cannot be separated from the teaching and learning process. An English teacher must carry out the teaching and learning process and class assessment. However, not all English teachers really understand and have a good perception of English language assessment and apply English language assessment correctly to measure students' English abilities based on indicators that students must master. This research aims to determine: English teachers' perceptions of English language assessment; carrying out English language assessments; and the correspondence between their perceptions and the implementation of the English language assessment. This research uses a qualitative case study involving 20 English teachers. Data collection was carried out using questionnaires, observation and document analysis. Data validity was carried out using triangulation of techniques and sources. Data analysis was carried out using an interactive analysis model which includes data condensation, data presentation, drawing conclusions and verification. The research results show that: most English teachers have good and positive perceptions of English language assessment; most English teachers implement English language assessments; and there is a match between their perceptions and the application of English language assessment in the teaching and learning process. Implications of this research shows that it is important to align English language assessment policies with the realities of practice on the ground.